(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this work, the concept of fuzzy set, mathematical theories based on these sets, their practical importance is highlighted. Relationships between fuzzy sets and actions performed on them are explained on the basis of specific examples.